Visualising latent DNA on swabs. (October 2018) - Kanokwongnuwut, P.; Kirkbride, P.; Linacre, A.
Highlights: Described is a new fluorescence microscopy-based method to visualise latent DNA on swabs. Three swab types were found to be effective for collection of biological material, 7 were not effective. The fluorescence is still detectable with little reduction in brightness even if stained and then re-examined 4 weeks later. Fluorescence detection of 'aged' cellular material on swabs is effective. Abstract: Collection for touch DNA either at scenes or on items submitted to a forensic laboratory is based on assumptions as to where a person made direct contact. In many instances a swab may be applied to an area where no contact has been made. Many swabs may therefore be submitted for DNA profiling on which no DNA is present, resulting in the loss of both time and resources by analysing such swabs. This study has developed a simple, fast, DNA-staining and fluorescence microscopy-based screening method for swabs to indicate if there is any DNA from which to generate a profile. Ten different types of swabs were tested covering the major types used (foam, cotton and nylon). Each swab was treated by: no addition of dye or DNA, addition of dye only, addition of known DNA and addition of dye and DNA. The stain used was Diamond™ Nucleic Acid Dye (DD) and fluorescence microscopy was achieved with a digital microscope equipped with a blue LED light source (480 nm) for excitation and an emission filter of 510 nm. Two types of samples were tested, either buccal swabs or swabs collected from areas touched by volunteers and all analyses were performed in triplicate. The samples were collected and retained at room temperature with time intervals of 0 day, 7 days, 14 days, 21 days, and 28 days before detection using DD staining and fluorescence microscopy. Seven of the swab types used were found to be unsuitable due to the lack of any difference in the fluorescence detected when no DNA, or only the dye, or a combination of DNA and dye were added. Three swab types (black cotton swab, Ultrafine dental applicator, and Cylinder dental applicator) were found to be much more effective for collection of DNA. Further, stained cellular material retained its fluorescence for up to 4 weeks and swabs containing cellular material that had been stored for four weeks could be stained and visualised. Additionally, DD did not affect DNA profiling. This screening method has the potential to be a routine step in a forensic laboratory to save costs of processing samples where swabs are devoid of any DNA. This technique is rapid, easy, cheap, non-destructive and safe.